Factors predicting leaving against medical advice in Neurosurgery: A prospective observational study from Nepal - Sapkota, Shabal; Karn, Mitesh; Neupane, Bhoj Raj; Gurung, Bandana; Pandit, Chandika; Upadhyay, Tirtha; Sigdel, Brihaspati; Kandel, Dipendra (Nepal Journal of Neuroscience, 2022)
Introduction: Though leave against medical advice (LAMA) is a common healthcare problem in low-income countries, there is paucity of studies exploring this aspect of care from Nepal. Our study aims to find out the prevalence of LAMA, its reasons and any differences that exist among patients in neurosurgery versus other specialties.Methods: A prospective, cross-sectional study was carried out among patients discharged against medical advice from September 2020 through February 2021 at Gandaki Medical College, Pokhara.      Results: A total of 150 patients were included, 29.3% (n=44) from neurosurgery and 70.7% (n=106) from other departments. The overall rate of LAMA was 5.68%; 16.73% from neurosurgical service. In the neurosurgical cohort, mean age was 61.41±18.72 years and majority of patients were males (65.9%). Most patients were Hindu by religion (97.7%), illiterate (59.1%), married (93.2%), with history of substance abuse (63.6%), admitted directly to the ICU (88.6%) and lacked insurance (79.5%). Financial insufficiency (40.9%) followed by expected poor prognosis of the disease (25%) were reported as major reasons for LAMA. Statistically significant differences (p